3, 3′‐Diamino‐N‐methyldipropylamine as a versatile affinity ligand. Issue 5 (3rd February 2015) - Silva, Marta S.; Graça, Vânia C.; Reis, Lucinda V.; Santos, Paulo F.; Silvestre, Samuel; Granadeiro, Luiza; Almeida, Paulo; Queiroz, João A.; Sousa, Fani
<x xml:space="preserve">Abstract</x> Currently, in biomedicine and biotechnology fields, there is a growing need to develop and produce biomolecules with a high degree of purity. To accomplish this goal, new purification methods are being developed looking for higher performance, efficiency, selectivity, and cost‐effectiveness. Affinity chromatography is considered one of the most highly selective methods for biomolecules purification. The purpose of this work is to explore a new type of a structurally simple ligand immobilized onto an agarose matrix to be used in affinity chromatography. The ligand in this study, 3, 3′‐diamino‐N‐methyldipropylamine has shown low toxicity and low cost of preparation. Moreover, the ability of the ligand to be used in affinity chromatography to purify proteins and nucleic acids was verified. An increasing sodium chloride gradient, using salt concentrations up to 500 mM, was suitable to accomplish the purification of these biomolecules, meaning that the new support allows the recovery of target biomolecules under mild conditions. Thus, the 3, 3′‐diamino‐N‐methyldipropylamine ligand is shown to be a useful and versatile tool in chromatographic experiments, with very good results either for proteins or supercoiled plasmid isoform purification.